The effect of gender on post-examination confidence in chemistry courses - Fana Mejia, M.; Murray, B.; Webb, J.A.; Karatjas, A.G. (Journal of College Science Teaching, 2024)
Interest in the gender gap in the physical sciences has been ongoing for a number of years. This study aimed to explore differences in gender based on self-perception. The use of a post-examination survey was used to examine the role of gender in grade perception in chemistry courses over a several-year period. This included courses for non-science majors, health science majors, and traditional chemistry courses for science majors. Self-reported data was collected after the completion of examinations and analyzed to explore the connection between gender and the student’s postdiction (a prediction after the completion of the examination) of their examination score as it related to the Kruger-Dunning effect. While male and female students followed the same general patterns, it was found that for most students, male students tended to predict higher scores than female students while seeing little difference in actual performance. The lowest performing students (those scoring less than 50% on examinations) showed little difference in the accuracy of their postdictions based on gender. © 2024 National Science Teaching Association.
Keywords: Chemistry; Exam preparation; Exams; Gender; Self-perception; dept.che; peer-reviewed